Baroquemania : Italian visual culture and the construction of national identity, 1898-1945 - Cecchini, Laura Moure (Manchester scholarship online., 2021)
Baroquemania offers a new account of Italian post-unification visual culture through its entanglement with the Baroque. Interrogating the Baroque's fraught afterlife in the work of Giorgio de Chirico, Armando Brasini, Lucio Fontana and others, the book reveals its role in crafting a distinctively Italian approach to modern art.